Bike helmets – a dangerous fixation? On the bike helmet's place in the cycling safety discourse in the United States. Issue 2 (3rd May 2020) - Culver, Gregg
Abstract: Despite the increasing popularity of the bicycle as a mode of urban transport in the United States, compared to much of the industrialized West, the US cycling scene continues to struggle with a high fatality and severe injury rate, and comparatively low levels of cycling. In contrast to the most bicycle-friendly countries, which have achieved high rates of safe cycling not through widespread adoption of bicycle safety helmets, but through bicycle-friendly infrastructure and policy, the US appears to have maintained a greater fixation on, and a higher rate of use of, bicycle helmets. In this paper, I seek to examine whether there is evidence of a helmet fixation, to sketch out the broad strokes of such a fixation as a discourse, and to offer an explanation of the effects of this discourse. Using a qualitative analysis of the official online presence of 25 US city planning departments relating to bicycling and bicycle safety, I first provide evidence that the helmet does in fact take a central place in the US urban bike safety discourse, and I characterize four rhetorical strategies used to encourage helmet use. I then argue that this helmet fixation is ultimately tied to the (re)production of unfettered automobility, and that it arguably hampers efforts to actually improve bicycle safety. I subsequently suggest implications for research, practice, and advocacy.